POLICY OF TRANSFERRING PRISONERS IN THE CATEGORY OF NARCOTICS DEALERS TO SUPERMAXIMUM SECURITY PENITENTIARY - Akhmad Muttaqien; Baharudin Baharudin; Lintje Anna Marpaung (Universitas Labuhanbatu, 2023)
The enactment of the Minister of Law and Human Rights Regulation Number 35 of 2018 concerning the Revitalization of Correctional Administration, one of which regulates the transfer of high-risk prisoners to Super maximum security prisons. Narcotics convicts who are at high risk are those who are included as dealers and narcotics controllers from within the prison. The purpose of this research are to analize: (1) Policy of transferring prisoners in the category of narcotics dealers to Supermaximum Security Penitentiary? Inhibiting factors for the policy of transferring prisoners in the category of narcotics dealers to the Supermaximum Security. The research using normative and juridical approach.Â The results of this study indicate: (1) The policy of transferring prisoners in the category of narcotics dealers to the Supermaximum Security Penitentiary was implemented by the Class II Narcotics Prison in Bandar Lampung by transferring 19 prisoners to the Class Special Prison. IIA Karanganyar Nusakambangan and Class IIA Nusakambangan Narcotics Prison. The policy has been implemented even though it has not been maximized, because there are still inhibiting factors. (2) The inhibiting factors for the policy of transferring prisoners in the category of narcotics dealers to the Supermaximum Security Penitentiary as an effort to cut off the circulation of narcotics are the risky behavior of prisoners in the category of narcotics dealers that endanger or have a negative impact on themselves, others and the environment and the process of evaluation and reassessment of prisoners who need a relatively long time.Keywords: Transfer Policy, Narcotics, Super Maximum Security